Gynecologic Oncology Sub-Specialty Training in Ghana: A Model for Sustainable Impact on Gynecologic Cancer Care in Sub-Saharan Africa - Erem, Anna Sarah; Appiah-Kubi, Adu; Konney, Thomas Okpoti; Amo-Antwi, Kwabena; Bell, Sarah G.; Johnson, Timothy R. B.; Johnston, Carolyn; Tawiah Odoi, Alexander; Lawrence, Emma R. (Frontiers in Public Health, 2020)
African women have double the risk of dying from cancer than women in high-income countries. In Ghana, cervical cancer is the second most common type of cancer in women, surpassed only by breast cancer. It accounts for one-quarter of cancers seen in women and is the leading cause of cancer-related death for Ghanaian women. Most Ghanaian women with gynecological malignancies present with advanced-stage disease when treatment is less effective. In Ghana, barriers to improved cancer outcomes include the availability of cervical cancer screening, affordability of treatment, and access to gynecologic oncology specialists. In response to a paucity of gynecologic oncology providers, an in-country fellowship training program was established at Komfo Anokye Teaching Hospital (KATH) in 2013. Historically, Ghanaian resident physicians were sent to other countries, most commonly the United States or the United Kingdom, for further medical education and fellowship training and were unlikely to repatriate. The establishment of an in-country training program not only addresses the challenge of “brain drain,” but also builds local capacity in gynecologic education and emphasizes culturally relevant and accessible healthcare. The four-year gynecologic oncology fellowship program at KATH was developed as part of a longitudinal multi-decade partnership between the University of Michigan and Ghana College of Physicians and Surgeons. Similar fellowships have led to graduates remaining in-country at much higher rates. The fellowship’s curriculum trains Obstetricians and Gynecologists (OBGYNs) to provide sub-specialist clinical and surgical care to patients with gynecologic malignancies. Fellows collaborate with the radiation, oncology and pathology departments, participate in monthly inter-institutional tumor board meetings, explore research problems, advise on health policy issues, and provide training to subsequent cohorts of trainees. Mentorship and on-site training for the program is provided in partnership with the University of Michigan. This fellowship is representative of emerging twenty-first-century trends in which sub-specialty training programs in low-income countries are strengthened by international collaborations. The challenges of finding funding and meeting local needs for specialized medical education, while maintaining rigorous standards, can often be overcome through global partnerships. Providing specialized training in gynecologic oncology can help develop and maintain resources that will provide Ghanaian women with better outcomes.